Degradation, Conservation, and Restoration of Works of Art: Historical Overview - Roger Marijnissen (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This extract presents the preliminary reflections to the book  Degradation, preservation, restoration of the work of art, Brussels, Arcades, 1967.